Research on gob-side entry retaining technology inclined fully mechanized mining face with large mining height - Teng LI; Yongdong JIANG; Huajun LIU; Yong ZOU; Tao GUI; Fei CHEN (Meitan kexue jishu)
In order to solve obvious dynamic pressure and support problems of gob-side entry retaining in steeply inclined fully-mechanized mining face with large mining height, taking 31111 fully-mechanized mining face in Shidonggou Coal Mine of Sichuan Coal Group as the research background, through theoretical analysis and field monitoring, the periodic weighting step of 31111 fully mechanized mining face is about 16.4 m, and the influence range of abutment pressure in front of coal wall is about 40 m. The advance support distance of 31111 roadway is defined. Combined with the three-dimensional positioning technology of microseismic monitoring, the range of ' three zones ' ( the influence zone of abutment pressure of coal wall is about 40 m, the separation zone is 122～144 m ) and ' three zones ' ( the caving zone of roof is 0～2 m, the fracture zone is 2～30 m, and the bending subsidence zone is 30～96 m ) of 31111 fully mechanized mining face is obtained, and the periodic fracture law of steeply inclined and large mining height strata and the characteristics of '厂' type moving arch are revealed, which provides data support for subsequent pressure prediction and implementation of gob-side entry retaining. Based on the deformation and pressure distribution law of roadway surrounding rock in the mining process, the method of gob-side entry retaining with bow-shaped flexible shield support + anchor net cable combined support is proposed in the non-fault zone, and the method of gob-side entry retaining with bow-shaped flexible shield support + anchor net cable + gangue cemented filling combined support is proposed in the fault zone. The field engineering practice shows that the method is rigid and flexible, which has a good supporting and shielding effect on the caving gangue in the goaf, ensures the safety of gob-side entry retaining, and realizes the safe and economic mining without coal pillar in the mine.